Cultivating a culture of intervention: Bystander programs and the prevention of sexual violence - Marhayati, Nelly; Suryani, Suryani; Badriyah, Lailatul; Sitorus, Iwan Ramadhan (Edelweiss Applied Science and Technology, 2024)
This systematic review examines the effectiveness of bystander intervention programs in preventing sexual violence, with a focus on the role of masculinity and cultural factors. The review synthesizes findings from six studies, employing a mixed-methods approach to analyze quantitative and qualitative data. The results highlight the significance of bystander intervention in preventing sexual violence, particularly among young people. The studies demonstrate that programs targeting men and boys, addressing traditional masculinity norms, and promoting empathy and prosocial behavior are effective in reducing sexual violence. Cultural factors, such as social norms and community engagement, also play a crucial role in shaping bystander behavior. The review concludes that bystander intervention programs have the potential to create a culture of empathy and action, but require careful consideration of cultural context and nuances. The findings have implications for the development of effective prevention strategies and highlight the need for further research in this area. By understanding the complexities of bystander behavior, we can work towards creating safer and more supportive communities for all individuals.